Features of pedagogical creativity and factors of its development in future teachers (Pedagogy of Higher and Secondary Education, 2012)
Pinska O. L. Features of pedagogical creativity and factors of its development in future teachers.The article reveals the nature and characteristics of educational work, substantiate the factors that determine the effectiveness of its development.
Keywords: art; teaching art; cocreation